2017
DOI: 10.1128/aem.01354-17
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Repeated Glyphosate Use on Wheat-Associated Bacteria Are Small and Depend on Glyphosate Use History

Abstract: Glyphosate is the most widely used herbicide worldwide and a critical tool for weed control in no-till cropping systems. However, there are concerns about the nontarget impacts of long-term glyphosate use on soil microbial communities. We investigated the impacts of repeated glyphosate treatments on bacterial communities in the soil and rhizosphere of wheat in soils with and without long-term history of glyphosate use. We cycled wheat in the greenhouse using soils from 4 paired fields under no-till (20+-year h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
31
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 50 publications
9
31
1
2
Order By: Relevance
“…And while both barcoding and culture surveys detected other pathogens, none responded to glyphosate (Supplementary Data). Our results are consistent with previous metabarcoding studies [20, 21].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…And while both barcoding and culture surveys detected other pathogens, none responded to glyphosate (Supplementary Data). Our results are consistent with previous metabarcoding studies [20, 21].…”
Section: Discussionsupporting
confidence: 94%
“…Greenhouse studies with GR wheat conducted in the Pacific Northwest found only minor effects of glyphosate on microbial communities, and determined site was a major driver of soil microbial community structure [20, 21]. While these studies did detect effects of glyphosate on the prevalence of a few microbial taxa, they applied glyphosate at twice the recommended rate, increasing the likelihood that the microbial community experienced a significant effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed that the exposure of honeybees to glyphosate alters the bee gut microbiota and increases the susceptibility to infection by opportunistic pathogens like Serratia marcescens (Motta et al, 2018). In contrast, a role of glyphosate in affecting the soil microbial activity is controversially discussed because studies are available suggesting a positive and a negative effect of the herbicide on the microbial activity of the soil (Haney et al, 2002;Barriuso et al, 2011;Schlatter et al, 2017;Dennis et al, 2018). Thus, the effect of glyphosate on the bee microbiota seems to be unambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effect of glyphosate on the bee microbiota seems to be unambiguous. In contrast, a role of glyphosate in affecting the soil microbial activity is controversially discussed because studies are available suggesting a positive and a negative effect of the herbicide on the microbial activity of the soil (Haney et al, 2002;Barriuso et al, 2011;Schlatter et al, 2017;Dennis et al, 2018). Moreover, the intensive use of the herbicide clearly stimulates the evolution of glyphosate-resistant plants and the use of genetically modified glyphosate-resistant crops decreases the diversity and abundance of wild plants (Heap, 2014;Schütte et al, 2017;Bagavathiannan and Davis, 2018).…”
Section: Introductionmentioning
confidence: 99%